2019
DOI: 10.1111/jcmm.14380
|View full text |Cite
|
Sign up to set email alerts
|

Alisol A attenuates high‐fat‐diet‐induced obesity and metabolic disorders via the AMPK/ACC/SREBP‐1c pathway

Abstract: Obesity and its associated metabolic disorders such as diabetes, hepatic steatosis and chronic heart diseases are affecting billions of individuals. However there is no satisfactory drug to treat such diseases. In this study, we found that alisol A, a major active triterpene isolated from the Chinese traditional medicine Rhizoma Alismatis, could significantly attenuate high‐fat‐diet‐induced obesity. Our biochemical detection demonstrated that alisol A remarkably decreased lipid levels, alleviated glucose metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 51 publications
(83 reference statements)
3
29
0
Order By: Relevance
“…In the human hepatic stellate cell line LX-2 cells modeled with MCD medium, Alisol A can regulate autophagy via the AMPK/mTOR/ULK1 pathway, it can also suppress reactive oxygen species (ROS) and inflammation in MCD mouse model [ 46 ]. Besides that, Alisol A cannot alleviate lipid and glucose metabolism, but also reduce hepatic steatosis and improve liver function in HFD mice [ 47 ]. In vitro, AA24A significantly reduces the number of lipid droplets, oil red O lipid content and triglyceride (TG) content in cells treated with palmitic acid [ 48 ].…”
Section: Effects and Mechanisms Of Commonly Used Single Herb Drugs In Tcm On Nafldmentioning
confidence: 99%
“…In the human hepatic stellate cell line LX-2 cells modeled with MCD medium, Alisol A can regulate autophagy via the AMPK/mTOR/ULK1 pathway, it can also suppress reactive oxygen species (ROS) and inflammation in MCD mouse model [ 46 ]. Besides that, Alisol A cannot alleviate lipid and glucose metabolism, but also reduce hepatic steatosis and improve liver function in HFD mice [ 47 ]. In vitro, AA24A significantly reduces the number of lipid droplets, oil red O lipid content and triglyceride (TG) content in cells treated with palmitic acid [ 48 ].…”
Section: Effects and Mechanisms Of Commonly Used Single Herb Drugs In Tcm On Nafldmentioning
confidence: 99%
“…It remains to be explored whether these actions of alisol A are mediated by activation of PPARa and PPARd. It was reported that alisol A can activate the phosphorylation of AMPK (Ho et al, 2019). AMPK reduces lipid accumulation by regulating the expression of PPARa (Chen et al, 2013;Kang et al, 2015), whereas histone deacetylase SIRT1 senses the level of energy and helps cells to resist external stress and improve metabolism (Stein and Matter, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The 5'-adenosine monophosphate-activated protein kinase (AMPK) has been reported as an important regulator of cell metabolism (Fisslthaler and Fleming, 2009). It exerts anti-atherosclerotic action through reducing the activation of NF-kB (Li et al, 2020), promoting phosphorylation of acetyl-CoA carboxylase (ACC) to inhibit liver lipid synthesis (Ho et al, 2019), and inhibiting mTOR to enhance autophagy of macrophages (Yang et al, 2018). In addition, activation of AMPK increases intracellular nicotinamide adenine dinucleotide (NAD+) levels and activates Sirtuin 1(SIRT1) to protect the heart (Cantoé t al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…), Lycium barbarum polysaccharide, Jatrorrhizine hydrochloride, oxyresveratrol, and alisol A isolated from Rhizoma alismatis (Oriental Waterplantain Tuber.) attenuated liver steatosis in HFD-fed animals via regulating lipogenic genes, predominantly relating with downregulation of SREBP-1c expression via AMPK activation Li W. et al, 2014;Lee Y. H. et al, 2016;Yang et al, 2016;Lee et al, 2018;Lim et al, 2018;Ho et al, 2019). Gangjihwan, a polyherbal composition of Ephedra intermedia Schrenk & C.A.Mey., Lithospermum erythrorhizon Siebold & Zucc., and Rheum palmatum L., showed anti-obesity and antinonalcoholic steatohepatosis effects in HFD-fed mice.…”
Section: Reducing Hepatic De Novo Lipogenesismentioning
confidence: 99%